Knowledge attribution, socioeconomic status, and education: new results using the Great British Class Survey. - de Bruin, Boudewijn (Synthese, 2021)
This paper presents new evidence on the impact of socioeconomic status (SES) and education on knowledge attribution. I examine a variety of cases, including vignettes where agents have been Gettiered, have false beliefs, and possess knowledge (according to orthodoxy). Early work investigated whether SES might be associated with knowledge attribution (Weinberg et al. in Philos Top 29(1–2):429–460, 2001; Seyedsayamdost in Episteme 12(1):95–116, 2014). But these studies used college education as a dummy variable for SES. I use the recently developed Great British Class Survey (Savage et al. in Sociology 47(2):219–250, 2013) to measure SES. The paper reports evidence against an association between SES and patterns of knowledge ascription, and reports mixed evidence about education effects.